Acute Kidney Injury in Neonates in the PICU*. Issue 4 (April 2016) - Kriplani, Disha S.; Sethna, Christine B.; Leisman, Daniel E.; Schneider, James B.
Abstract : Objectives: Acute kidney injury is an independent risk factor for morbidity and mortality in critically ill children in the PICU. Neonates are a particularly vulnerable subgroup regarding acute kidney injury. The objectives were to define the prevalence of acute kidney injury to assess independent risk factors, for the development of acute kidney injury, and to determine the impact of acute kidney injury on outcomes in critically ill neonates without history of cardiac surgery. Design: A retrospective study of neonates (⩽ 28 d old and ≥ 32 wk of gestational age) admitted to a tertiary PICU was conducted. Acute kidney injury was classified using the Kidney Disease: Improving Global Outcomes definition. Setting: PICU in a tertiary children's hospital. Patients: A total of 80 neonates (62% male neonates) with a median gestational age of 38 weeks (interquartile range, 37–39 wk) were reviewed. Intervention: None. Measurement and Main Results: Acute kidney injury was found in 35% ( n = 28) of neonates. Fourteen (50%) reached stage I, 8 (29%) stage II, and 6 (21%) stage III acute kidney injury. Younger age was associated with acute kidney injury ( p = 0.016; odds ratio, 0.93; CI, 0.88–0.98). In regression analysis adjusted for age and gender, bacteremia ( p = 0.014; odds ratio, 5.4; CI, 1.4–20.4) and maximum sodium concentration ( p = 0.02; odds ratio, 1.12; CI, 1.02–1.24) were associated with acute kidney injury. Mortality ( p = 0.03) and length of mechanical ventilation ( p = 0.001) were significantly higher in neonates with acute kidney injury compared with those without acute kidney injury. In an adjusted regression model, stages 2 and 3 combined were associated with increased mortality ( p = 0.02; odds ratio, 5.64; CI, 1.33–23.8), length of ventilation ( p = 0.016; β, 12.2; CI, 2.39–22.0), and length of stay ( p = 0.049; β, 12.2; CI, 0.073–24.3). Conclusions: Acute kidney injury is common in neonates not requiring cardiac surgery and is associated with increased morbidity and mortality. Age, bacteremia, and maximum sodium concentration are independently associated with the development of acute kidney injury in this population.